Anti-angiogenic therapy with contrast-enhanced ultrasound in colorectal cancer patients with liver metastasis. Issue 20 (May 2017) - Wu, Zhiyong; Yang, Xiaowei; Chen, Li; Wang, Zhikuan; Shi, Yan; Mao, Hui; Dai, Guanghai; Yu, Xiaoling
Abstract : Abstract: The aim of the study was to evaluate the efficacy of anti-angiogenic therapy with dynamic contrast-enhanced ultrasound (DCE-US) in colorectal cancer (CRC) patients with liver metastasis. A total of 50 CRC patients with liver metastasis who received bevacizumab (BEV)-based chemotherapy (BEV + FOLFOX6 protocol) were recruited into the present study. Before the study (d0), and 3, 7, 14, and 42 days (d3, d7, d14, and d42) after chemotherapy, DCE-US was performed, and tumor perfusion was evaluated quantitatively by retention time (RT), peak enhancement (PE), and wash-in area under the curve (WiAUC) on the basis of a contrast-uptake curve determined with original linear data. Routine ultrasonography was used to evaluate metastatic foci in the liver at baseline. A metastatic focus was selected for dynamic monitoring with ultrasound. The metastatic foci were 1.5 to 8 cm (median: 2.5 cm). The results of hemodynamics monitored at different time points, including RT, PE, and WiAUC, showed that RT at baseline was significantly different between groups ( P  < .001; Responder group: 10.54 seconds; nonresponder group: 15.33 seconds). The2 groups had opposite changes in RT (continuous increase in the responder group and transient reduction in the nonresponder). The RT of metastatic foci was normalized to that of adjacent normal liver as standard RT-quotient, a similar trend was observed, and no marked difference was noted in the standard RT-quotient between the 2 groups. The median progression-free survival was significantly higher in the increased-RT group (10.8 months) than the decreased-RT group (2.5 months) ( P  = .002). There were no significant differences in peak intensity and WiAUC between the 2 groups. DCE-US can be used to quantitatively evaluate the hemodynamics of liver metastasis in CRC patients who received bevacizumab-based chemotherapy.